A study of road hazards faced by Malaysian school children using HIRARC - Ahmad Rasdan Ismail; Noor Adilah Hamzah; Nor Kamilah Makhtar; Nurul Husna Che Hassan; Darliana Mohamad; Baba Md Deros (2018)
Road transport is the movement of passengers or goods on the road. To date, issues concerning the safety of students and school institutions have continued to attract public attention. The recent spate of incidents insideandoutside the school compound has brought the issue ofchildren safetyinto our attention. These include the escalating number of road casualties. This study was conducted to observe roadhazard outside the school compound and analyse the safety risksfaced by school childrenby using the risk matrix. The risks arecalculated to includelikelihood and severity of hazard as identified in theGuideline of HIRARC 2008. The area selected was the East Coaststateof Peninsular Malaysia, withover 111 schools randomly selected in Kelantan. Re sults werethen analysed and six highlighted hazards were discussed. The results show that the main road posed the highest risk due to speeding vehicles. These vehicles failed to slow down when approaching the school area. The school administration must enhance the safety ofthe staff, students, and public while in the school area. In conclusion, road safety awareness must be instilled among teachers, students, parents and road users alike.